2017
DOI: 10.1590/s1806-37562016000000177
|View full text |Cite
|
Sign up to set email alerts
|

Family caregiver burden: the burden of caring for lung cancer patients according to the cancer stage and patient quality of life

Abstract: Objective: Patients with lung cancer experience different feelings and reactions, based on their family, social, cultural, and religious backgrounds, which are a source of great distress, not only for the patients but also for their family caregivers. This study aimed to evaluate the impact that lung cancer stage and quality of life (QoL) of lung cancer patients have on caregiver burden. Methods: This was a prospective cross-sectional study. Consecutive patient-caregiver dyads were selected and asked to comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
72
1
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 26 publications
7
72
1
14
Order By: Relevance
“…Assessment of the owners' hrQoL also might provide important information that can impact pets' care. Studies in people have shown that heart failure is associated with a high burden on the caregiver 10‐12 . Therefore, assessment of caregiver hrQoL can help to quantify an individual caregiver's burden and identify resources to address challenges and concerns that affect both the caregiver and the pets with cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the owners' hrQoL also might provide important information that can impact pets' care. Studies in people have shown that heart failure is associated with a high burden on the caregiver 10‐12 . Therefore, assessment of caregiver hrQoL can help to quantify an individual caregiver's burden and identify resources to address challenges and concerns that affect both the caregiver and the pets with cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…Two instruments have been validated for the assessment of hrQoL for the caregivers of human heart failure patients 13,14 . Improving caregiver hrQoL can improve human patients' hrQoL and outcomes 10‐12 . This might be even more important in veterinary medicine given the option for euthanasia, where cost of care, prognosis given to the owner by the clinician, and QoL are all important factors in the decision‐making process 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Up to 30% of caregivers of lung cancer report clinical depressive symptoms . Caregivers' higher depressive levels were associated with patients' high symptom distress, poor physical functioning, and advanced disease severity and caregivers' lack of support from others . Family caregivers often experience lack of time for self‐care, as well as decreased physical energy, social activities, and employment, which influences their physical and mental health .…”
Section: Introductionmentioning
confidence: 99%
“…4 Caregivers' higher depressive levels were associated with patients' high symptom distress, poor physical functioning, and advanced disease severity and caregivers' lack of support from others. 2,5,6 Family caregivers often experience lack of time for self-care, as well as decreased physical energy, social activities, and employment, 7,8 which influences their physical and mental health. 1,2,6 The stress from caregiving not only increases risk for depression 2 but also reduces their quality of care for their family members with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiver burden is a subjective feeling of stress that occurs when the demands of caregiving overwhelm caregiver resources to cope with those demands [2,3]. Patient factors (such as advanced cancer stage [4], health status [5], increased symptom burden, and decreased quality of life [QOL] [6][7][8]), caregiver factors (such as female gender [6,7,[9][10][11], age [5,10,[12][13][14], comorbidity [5], relationship to patient [15], education [14], and employment status [10]), and caregiving characteristics (such as increased duration of caregiving [7] and more help required by the patient [6,10,14]) are associated with increased caregiver burden. This information is typically obtained from patients or their caregivers.…”
Section: Introductionmentioning
confidence: 99%